PENGARUH EKSTRAKURIKULER PALANG MERAH REMAJA (PMR) TERHADAP SIKAP SOSIAL SISWA SMA - Redy Octama; Adelina Hasyim; Muhammad Mona Adha (Jurnal Kultur Demokrasi, 2013)
The goals of this research tell about the influences of extracurricular intence activity Youth Red Cross toward the social attitude to students in SMA Negeri 1 Kotaagung Tanggamus regency academic years 2012/2013. The method used in this research is descriptive method. The population in this research is the students that have been joining in extracurricular Youth Red Cross at the grades X and XI in SMA Negeri 1 Kotaagung academic years 2012/2013 with 35 despondences. The data in this research collected from questionnaire and documentation. Moreover, the technique data analysis using coefficient contingence formula or Chi quadrates. The results of this research shown that: the influences of extracuricular intence activity Youth Red Cross the dominant of good enough category with percentage 48,6% and the influences of extracuricular intence activity youth red cross toward the changing of social attitude to students dominant of high category with percentage 60%. And then known that there are significance influences of extracuricular intence activity youth red cross toward the changing of social attitude to students.Penelitian ini bertujuan menjelaskan pengaruh intensitas kegiatan ekstrakurikuler palang merah remaja (PMR) terhadap perubahan sikap sosial siswa. Metode yang digunakan dalam penelitian ini adalah metode deskriptif. populasi dalam penelitian ini adalah siswa yang berjumlah 35 orang responden. Data dalam penelitian ini dikumpulkan melalui angket dan dokumentasi, adapun teknik analisa data menggunakan rumus koefisien Chi Kuadrat. Hasil penelitian menunjukkan bahwa: pengaruh intensitas kegiatan ekstrakurikuler palang merah remaja (PMR) dominan pada kategori cukup baik dengan persentase 48,6%, dan pengaruh intensitas kegiatan ekstrakurikuler palang merah remaja (PMR) terhadap perubahan sikap sosial siswa dominan pada kategori tinggi dengan persentase 60%. Dengan demikian diketahui bahwa terdapat pengaruh yang cukup signifikan pada intensitas kegiatan ekstrakurikuler palang merah remaja (PMR) terhadap perubahan sikap sosial siswa.Kata kunci : intensitas kegiatan ekstrakurikuler, palang merah remaja, sikap sosial siswa